Identity Formation in Adolescence: Change or Stability? - Klimstra, Theo A. (Springer US, 2009)
The aim of this five-wave longitudinal study of 923 early to middle adolescents (50.7% boys; 49.3% girls) and 390 middle to late adolescents (43.3% boys and 56.7% girls) is to provide a comprehensive view on change and stability in identity formation from ages 12 to 20. Several types of change and stability (i.e., mean-level change, rank-order stability, and profile similarity) were assessed for three dimensions of identity formation (i.e., commitment, in-depth exploration, and reconsideration), using adolescent self-report questionnaires. Results revealed changes in identity dimensions towards maturity, indicated by a decreasing tendency for reconsideration, increasingly more in-depth exploration, and increasingly more stable identity dimension profiles. Mean levels of commitment remained stable, and rank-order stability of commitment, in-depth exploration, and reconsideration did not change with age. Overall, girls were more mature with regard to identity formation in early adolescence, but boys had caught up with them by late adolescence. Taken together, our findings indicate that adolescent identity formation is guided by progressive changes in the way adolescents deal with commitments, rather than by changes in the commitments themselves.